Altered function of ventral striatum during reward-based decision making in old age - Mell, Thomas; Wartenburger, Isabell; Marschner, Alexander; Villringer, Arno; Reischies, Friedel M.; Heekeren, Hauke R. (Frontiers in Human Neuroscience, 2009)
Normal aging is associated with a decline in different cognitive domains and local structural atrophy as well as decreases in dopamine concentration and receptor density. To date, it is largely unknown how these reductions in dopaminergic neurotransmission affect human brain regions responsible for reward-based decision making in older adults. Using a learning criterion in a probabilistic object reversal task, we found a learning stage by age interaction in the dorsolateral prefrontal cortex (dlPFC) during decision making. While young adults recruited the dlPFC in an early stage of learning reward associations, older adults recruited the dlPFC when reward associations had already been learned. Furthermore, we found a reduced change in ventral striatal BOLD signal in older as compared to younger adults in response to high probability rewards. Our data are in line with behavioral evidence that older adults show altered stimulus reward learning and support the view of an altered fronto-striatal interaction during reward-based decision making in old age, which contributes to prolonged learning of reward associations.